Absolute quantification of a therapeutic domain antibody using ultra-performance liquid chromatography–mass spectrometry and immunoassay. (September 2010) - Szapacs, Matthew E; Urbanski, James J; Kehler, Jonathan R; Wilson, Robert; Boram, Sharon L; Hottenstein, Charles S; Citerone, David R
Background: Domain antibodies (dAbs; ∼10–15 kDa) are made up of the variable heavy chain or the variable light chain of the antibody structure, and retain binding capability. dAbs have proved difficult to detect in plasma using immunoassay without specific antibodies raised against the dAb.Results: A sensitive and selective UPLC–MS/MS method for the absolute quantification of a dAb in monkey plasma was developed (range: 1 to 500 ng/ml) without the need for a specific capture antibody. This method was used to analyze pharmacokinetic studies early on in drug development. Furthermore, an immunoassay was developed and the pharmacokinetic samples were reanalyzed.Conclusion: The two assays show good correlation (r 2 = 0.92), giving confidence in using either method for quantification of the dAb.